Kerja Sama Selatan-Selatan: Strategi untuk Mengurangi Ketergantungan pada Bantuan Kemanusiaan - Muhammad Fajhriyadi Hastira (Universitas Pelita Harapan, 2025)
This study aims to explore South–South Cooperation (SSC) strategies in reducing the structural dependence of recipient countries on traditional donors in humanitarian aid, using the dependency theory framework as an analytical tool. The method used is descriptive qualitative, based on literature review, where data were collected through systematic searches in Scopus using the keywords “South–South Cooperation,” “dependency theory,” and “humanitarian aid dependency.” Analysis was conducted using content analysis techniques: data reduction, thematic presentation, and triangulation of sources to ensure validity. The results of the study reveal three main strategies of SSC, namely (1) demand-driven technology transfer tailored to local needs, (2) technical training and institutional capacity building, and (3) a horizontal approach among countries that eliminates political conditionalities. Empirically, regression analysis of 27 projects showed an average decrease in external supply dependency of 34% and an increase in the institutional resilience index of 41% over three years of implementation. The main contribution of this study is to expand theoretical understanding of counter-dependency mechanisms and provide practical recommendations for responsive foreign policy, including developing a standardized monitoring-evaluation framework and strengthening regional training centers.